2007
DOI: 10.1002/ejic.200700784
|View full text |Cite
|
Sign up to set email alerts
|

Flexible CuI–Thiolate Clusters with Relevance to Metallothioneins

Abstract: Simple Cu-thiolate chemistry was developed to demonstrate the presence of copper clusters with {Cu 4 S 6 }, {Cu 5 S 7 } and {Cu 6 S 4 } cores in relevance to copper-containing metallothioneins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
2
32
1
Order By: Relevance
“…The Cu À S bond lengths (av 2.295(2) ) are dependent on the coordination modes of the sulfur atom and distinct ranges can be distinguished: (2.2692 for CuÀm 2 -S, 2.2822 for CuÀm 3 -S, and 2.3312 for Cu À m 4 -S in 4). The Cu À S bond lengths are similar to those found in trigonal copper complexes with thiourea ligands, [24] but are significantly longer than the bond lengths of the tetrahedral CuS 4 unit observed in ternary or quaternary copper tin sulfides. [7,31,32] The Nd 3 + , Gd 3 + , and Er 3 + ions are coordinated to four en ligands with formation of distorted bicapped trigonal prisms LnN 8 ( Figure S11 in the Supporting Information).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The Cu À S bond lengths (av 2.295(2) ) are dependent on the coordination modes of the sulfur atom and distinct ranges can be distinguished: (2.2692 for CuÀm 2 -S, 2.2822 for CuÀm 3 -S, and 2.3312 for Cu À m 4 -S in 4). The Cu À S bond lengths are similar to those found in trigonal copper complexes with thiourea ligands, [24] but are significantly longer than the bond lengths of the tetrahedral CuS 4 unit observed in ternary or quaternary copper tin sulfides. [7,31,32] The Nd 3 + , Gd 3 + , and Er 3 + ions are coordinated to four en ligands with formation of distorted bicapped trigonal prisms LnN 8 ( Figure S11 in the Supporting Information).…”
Section: Introductionsupporting
confidence: 62%
“…The CuÀS bond lengths vary from 2.289(6) to 2.314(6) , and the S-Cu-S angles from 115.0(2) to 123.2(2)8, which are in the range of the corresponding values observed in other trigonal CuS 3 units. [24] In 1, the S atoms exhibit terminal (S4, S7, S9), m-S (S2, S3, S5, S6), S8) bridging, and m 3 -S (S1) bridging coordination modes with the tin and copper atoms. A m 3 -S bridging ligand which bonds to three different metal centers (Sn, Cu and La) has not been observed before.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand system comprises two nitrogen donors and the connecting thiolate functions. Sarkar et al reported different systems with pure bidentate dithiolate ligands , . For example, the tetranuclear thiolate‐bridged [Cu 4 {S 2 C 2 (CN) 2 } 4 ] 4– complex anion can serve as a host framework .…”
Section: Resultsmentioning
confidence: 99%
“…Sarkar et al reported different systems with pure bidentate dithiolate ligands , . For example, the tetranuclear thiolate‐bridged [Cu 4 {S 2 C 2 (CN) 2 } 4 ] 4– complex anion can serve as a host framework . Without the two CuCl units, the ring structure of C1 and C2 is comparable despite the different coordination environment of the copper atoms evoked by the phenanthroline ligands and the charge caused by the two thiolate functions in [Cu 4 {S 2 C 2 (CN) 2 } 4 ] 4– .…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] One of the other typical emissive states is the triplet cluster-centered ( 3 CC) excited state that is usually observed for the iodide-bridged Cu I cluster complexes. [42][43][44][45] An interesting feature is the external-stimuli-responsive luminescence such as thermochromic, vapochromic, and mechanochromic luminescencet hat may be applicable to varioust ypes of sensors. [17][18][19][20][21][22][23][24][25][26][27][28] For example, interesting thermochromic luminescence has been observed for cubane-type Cu I cluster complexes [Cu 4 I 4 (py) 4 ]a nd [Cu 4 I 4 (PPh 3 ) 4 ]( py = pyridine, PPh 3 = triphenylphosphine).…”
Section: Introductionmentioning
confidence: 99%